A motivação no serviço público federal: o caso da perícia criminal federal - Gualda, Cristina Moniz de Aragão (2013)
This study aimed to identify whether the Federal Criminal Forensic Scientists who exercis e their activities in Forensic Science function are motivated to perform their duties and seek to relate the causes of demotivation. Therefore, we made two surveys: a qualitative order, where were interviewed ten (10) Federal Criminal Forensic Scientists , belonging to different areas of knowledge and working in different cities , in order to observe what do the se professionals indicate as their issues related to motivating or demotivating in their job . Later we designed a questionnaire consisting of 46 (fort y - six) closed questions and 2 (two) open questions , which w ere answered by Federal Criminal Experts Forensic Scientists from decentralized units of Criminalistics in Federal Police, with the goal of mapping the m motivation. The results revealed in field re search concluded that the Federal Criminal Forensic Scientists are discouraged from the viewpoint of all the motivational theories addressed in this study. The de motivation is due to several factors: some technical, as the lack of feedback on the effective ness of the work or the lack of equality in the distribution of services, other than the philosophical factors , the lack of an esprit de corps - a professional identity – and a relativized autonomy , or , beside this, organizational factors , such as lack of recognition by the Federal Police, to the importance of Federal Criminal Forensic Science , or problems related to the management approach based on hierarchy and discipline. However, the problem most harmful - and therefore must be addressed urgently - is the organizational climate contaminated by disputes between classes, which is promoting a climate of hostility and discouragement, discouraging the growth of Criminalistics.